Településnevek Ung és Bereg vármegyében az I. világháborút megelőző két évtizedben - Bagdi, Róbert (Közép-Európai Közlemények, 2016)
The conflict of modernisation efforts and the ethnic question generated tensions (also) over the settlement names in Hungary during the dualistic era. Around 12 thousands different settlements existed in Hungary before World War I, but in many cases several settlements (in different districts) used identical names: 18 villages used for example the name of ‘Kisfalud’ according the Official Settlements’ Register in 1863. It also happened that a settlement had more than one name at the same time. The similar or the identical settlement names caused confusion during the everyday life, e. g. in connection with post, railway, or compulsory military services. The Law of 1898 ordered the Hungarian Register Committee of Settlements to assign one official name for each settlement (and also its orthography). More than half the settlements in Ung and Bereg County had got new official names by 1904. Geographical division of the settlements with new official names in Ung and Bereg County are shown on compiled maps. Many villages had new ‘Hungarian’, ‘or ‘Magyarized names’, e.g. Verbiás, Bablyuk, Ploszkópatak and Petruszavica united under the official name Verebes around the millennium. The Hungarian ‘Veréb’ means ‘Sparrow’ in English; however none of the original four names was connected to sparrows.